JAVANESE LANGUAGE AS AN ETHNIC IDENTITY MARKER AMONG MULTILINGUAL FAMILIES IN INDONESIA - Evynurul Laily Zen (Masyarakat Linguistik Indonesia, 2021)
The rise of a pan-Indonesian national identity and the global significance of English have weakened heritage languages in Indonesia’s various ethnolinguistic communities. Focusing on the case of Javanese, the largest ethnic group, this study examines the role of the HL as an ethnic marker and its interplay with factors such as ethnic self-identification, proficiency, and usage frequency. The data were collected via parental surveys of 183 primary school children in East Java. The findings indicate that the Javanese language is still highly valued as ethnic marker and that Javanese people view its maintenance as central to their identity construction. However, inconsistencies are identified between attitudes and practices, with use of Javanese as a home language decreasing, and children’s production showing extensive influence from Indonesian. Taken together, positive attitudes regarding the Javanese as identity marker and the apparent ethnolinguistic vitality of Javanese is not necessarily translated into intergenerational transmission.